Odpowiedzi

2009-12-08T17:01:59+01:00
3(x-y) +4x = 8
3(x- 5y)=5-9y

3x-3y+4x=8
3x-15y=5-9y

7x-3y=8
3x-15y+9y=5

7x-3y=8
3x-4y=5
Najlepsza Odpowiedź!
2009-12-08T17:04:27+01:00
3(x-y) +4x = 8
3(x- 5y)=5-9y

3x-3y+4x=8
3x-15y=5-9y

7x-3y=8 |*-2
3x-6y=5

-14x+6y=-16
3x-6y=5
-------------------
-11x=-11 |-11
x=1

3x-6y=5
3-6y=5

-6y=2 |/-6

y=-½
x=1





3(2x-1)+4 (y-2)=9
2(5x-1)+3y=5(3x+y)+2

6x-3+4y-8=9
10x-2+3y=15x+5y+2

6x+4y=20
-5x-2y=4 |*2

6x+4y=20
-5x-4y=8
--------------------
x=12

-5x-4y=8
-60-4y=8

-4y=52 |/-4

x=12
y=13



licze na naj




1 5 1